Performance analysis of band-limited DS-CDMA systems over generalized-k fading channels. - Haider Mehdi. (2010)
Direct-sequence spread-spectrum (DS-SS) has attracted considerable attention and has been adopted by many wireless communication vendors. Well-known communication systems employing DS-SS are based on the code-division multiple-access (CDMA) technique, such as global positioning system (GPS), wideband CDMA (WCDMA) system, etc. In practice, wireless channels are commonly modeled as a mixture of fading and shadowing. Various composite models have been reported in the literature. These models are based on lognormal distributions. The main disadvantage of these models is that they are mathematically complicated to analyze. Hence, the lognormal shadowing was approximated by a gamma shadowing leading to the K distribution and its generalized version, i.e., generalized-K distribution. This versatile distribution is useful in evaluating the performance of composite channels with simplicity and mathematical tractability. The BER performance of DS-CDMA systems has been extensively studied during the last two decades. However, most of the reported work is focused on DSCDMA systems with rectangular pulse-shaping, while in practice, band-limited pulse shapes are adopted. Therefore, the performance analysis of band-limited systems is of considerable interest, and has gained some interest in the recently published literature.